The impact of technology on the teaching and assessment of 'systems' diagrams in two online environmental management modules. (2nd January 2019) - Lane, Andy
Abstract: The context and tools used to create diagrams may hinder or help students in learning how to represent a situation and how to learn about diagramming and the situation at the same time. These equally provide opportunities and challenges to tutors in teaching, assessing and providing feedback on these diagrams, particularly for students studying at a distance. Two online undergraduate modules, dealing with environmental management at The Open University UK, require students to share diagrams with other students, to work collaboratively on diagrams in small groups and include diagrams in all assignments. This paper reports on students' and tutors' experiences of using diagrams before, during and outside involvement with both modules to better understand the main factors that influence their educational value, in particular the part that familiarity, experience and confidence in the techniques, the technologies and acts of sharing played in supporting learning or not.